2018
DOI: 10.1111/mec.14858
|View full text |Cite|
|
Sign up to set email alerts
|

A comparison of genomic islands of differentiation across three young avian species pairs

Abstract: Detailed evaluations of genomic variation between sister species often reveal distinct chromosomal regions of high relative differentiation (i.e., "islands of differentiation" in F ), but there is much debate regarding the causes of this pattern. We briefly review the prominent models of genomic islands of differentiation and compare patterns of genomic differentiation in three closely related pairs of New World warblers with the goal of evaluating support for the four models. Each pair (MacGillivray's/mournin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
156
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(182 citation statements)
references
References 85 publications
(188 reference statements)
16
156
1
Order By: Relevance
“…In addition, the presence of pronounced peaks of differentiation across the genome may indicate elevated selection within certain genomic regions, possibly related to the evolution of morphologically cryptic reproductive isolating mechanisms. Fewer peaks, on the other hand, may suggest a predominant role for neutral processes like genetic drift (Irwin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the presence of pronounced peaks of differentiation across the genome may indicate elevated selection within certain genomic regions, possibly related to the evolution of morphologically cryptic reproductive isolating mechanisms. Fewer peaks, on the other hand, may suggest a predominant role for neutral processes like genetic drift (Irwin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, computer models suggest that the effects of background selection on the divergence landscape may be modest (Zeng and Charlesworth 2011;Matthey-Doret and Whitlock 2018;Zeng and Corcoran 2018). Additionally, background selection has failed to explain some empirical patterns (e.g., Irwin et al 2016Irwin et al , 2018, and it may be the case that there has not been sufficient time for drift and/or negative selection to influence differentiation in recently diverged species (Burri 2017;Delmore et al 2018). Given these differing theoretical and empirical results, we used a comparative approach to disentangle the contributions of background selection and parallel positive selection to the repeatability of genomic differentiation in a recently diverged species.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent reinterpretation of these patterns, however, suggested that outlier peaks in FST could also be generated by reductions in within-population nucleotide diversity driven by "linked selection" (Noor and Bennett 2009;Cruickshank and Hahn 2014), either as a result of recent selective sweeps (Maynard Smith and Haigh 1974;Kaplan et al 1989;Stephan et al 1992;Braverman et al 1995;Gillespie 1997Gillespie , 2000Gillespie , 2001 or background selection (Charlesworth et al 1993;Charlesworth 1994;Hudson and Kaplan 1995;Gillespie 1997). Furthermore, some studies have demonstrated that genome-wide patterns in FST tend to be inversely correlated with both recombination rate and nucleotide diversity, suggesting that the search for the causal loci driving local adaptation may be obfuscated by the recombination and/or diversity landscapes across the genome (Burri et al 2015;Vijay et al 2017;Irwin et al 2018).…”
Section: Introductionmentioning
confidence: 99%